Wind regimes and aeolian geomorphology in the western and southwestern Tengger Desert, NW China. (12th August 2014) - Zheng‐cai, Zhang; Zhi‐bao, Dong; Qing, Wen; Chan‐wen, Jiang
Abstract : Wind is the primary control on the formation of aeolian geomorphology. In this study, we combined wind regime data from automated weather stations in the western and southwestern Tengger Desert of the Inner Mongolia region in China with remote‐sensing data to analyse the relationship between the wind energy environment and aeolian geomorphology. Tengger Desert is one of the main dust storm sources in northwestern China. Therefore, efforts aimed at controlling desertification and dust storm require a deeper understanding of the processes that govern the formation and subsequent evolution of dunes in this area. Wind speed was largest in the northwest (3.3 m/s in the Xiqu station) and smallest in the southeast (1.2 m/s in the Haizitan station). Potential sand transport was also largest in the northwest (195 in the Jiahe station) and smallest in the southeast (33 in the Tumen station). The sand‐driving wind (5.92 m/s) directions were from the NW and SE quadrant across the study area, at >76% of all sand‐driving wind, reaching 99% in the Tumen station. The sand‐driving wind in the NW quadrant reached >48%, and in the SE quadrant, >12% of all sand‐driving wind in all stations. In the study area, sand dunes included crescent, dune networks, transverse, and coppice dunes. Dune crest directions had similar trends from upwind to downwind, at 133° in the middle region, and 124° in the southwestern region. Mean dune spacing changed with dune patterns; the maximum spacing for crescent dunes was 147 m, for dune networks 118 m, and for transverse dunes it was 77 m. The mean crest length was 124 m (maximum) for crescent dunes in the northwest, 121 m for transverse dunes, and 84 m for dune networks. However, because of gullies in the southern region, the mean crest length was only 58 m (least) for the crescent dunes in that area. The defect density ranged from 0.007 to 0.014. The spatial differences in dune patterns reflected the evolution of the dune field, where older dunes had been formed upwind and younger downwind. Copyright © 2014 John Wiley & Sons, Ltd.